A Correlation between Vocabulary Mastery and Speaking Skill in Debate Performance of English Education Students - Nur Fatimah, Septi Dwi; Permana, Sindhuandra (Linguapedia, 2024)
This research aims to find a correlation between vocabulary mastery and speaking skill among English education students at Tidar University. This research used quantitative research which used correlational design. The sample of the students in this research was twenty-three students in the fifth semester of English Department taken randomly using cluster random sampling from all the population. The data of the research were collected by a quiz for the vocabulary mastery test and take the data from the previous semester's debate with the students. This result includes the 0,60-0,7999 interval that makes the correlation between vocabulary mastery and speaking skills of the students strong